2016
DOI: 10.4251/wjgo.v8.i1.128
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofRASandBRAFmutations on carcinoembryonic antigen production and pattern of colorectal metastases

Abstract: Author contributions: Fakih M designed and supervised the trial; Fakih M and Cho M wrote the paper; Telatar M, Afkhami M, Sentovich S and Melstrom K contributed to the analysis; Cho M, Akiba C and Lau C collected and analysed data; Smith D did the statistical analysis.Institutional review board statement: This study was reviewed and approved by the City of Hope National Medical Center.Informed consent statement: Patients were not required to give informed consent to the study because the analysis used anonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Poor survival outcome of BRAF mutation could be related to its propensity to metastasize frequently to poor prognostic sites like peritoneum and less frequently to liver or lung as seen in this study. However, incidence of peritoneal metastasis in BRAF mutant cancers shows wide variability, ranging from 10 to 45% [12,28]. Although there was no significant association seen between BRAF mutation, bony metastases and brain metastases, the numbers were too small to see any meaningful association.…”
Section: Braf Mutationmentioning
confidence: 91%
See 1 more Smart Citation
“…Poor survival outcome of BRAF mutation could be related to its propensity to metastasize frequently to poor prognostic sites like peritoneum and less frequently to liver or lung as seen in this study. However, incidence of peritoneal metastasis in BRAF mutant cancers shows wide variability, ranging from 10 to 45% [12,28]. Although there was no significant association seen between BRAF mutation, bony metastases and brain metastases, the numbers were too small to see any meaningful association.…”
Section: Braf Mutationmentioning
confidence: 91%
“…In addition, it has been increasingly recognized that biological behavior and prognosis of colorectal cancer may vary according to the location of the primary, BRAF, KRAS and MMR (mismatch repair) status, though data are not consistent [9,11]. Some retrospective analyses suggest these somatic and germ line mutations may have an impact on the pattern of metastasis, but most of these are small, uncontrolled and single institutional studies with varying associations [12,13]. The second part of this study was to investigate any association between molecular markers, site of primary and site of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival, months Survival probability Survival probability Survival probability Survival probability (27,28). The pattern of possible influence of the KRAS mutation on CA 19-9 excretion has not been well established yet.…”
Section: Discussionmentioning
confidence: 99%
“…CEA represents the only conventional and recognized blood-based test for monitoring recurrence and response to systemic therapy in CRC. The superiority of plasma ctDNA assays over CEA are quite evident, with even more applicability in the up to 34% of CEA non-producers in patients with CRC [ 151 ]. Furthermore, several groups have shown that the prognostic potential of ctDNA is independent of known clinicopathologic risk factors.…”
Section: Future Considerationsmentioning
confidence: 99%